The Extent of Teaching Staff's Awareness in the College of Educational Sciences - University of Jordan - of Teaching Competencies under the Principles of Total Quality - Abeer. M. I. Insaiw; Leena M. S. Alhyari (University of Science and Technology, Yemen, 2018)
This study aimed to investigate the extent to which the teaching staff members of the University of Jordan are aware of teaching competencies within the framework of total quality. The study population consisted of 172 faculty members from the College of Educational Sciences at the University of Jordan for the academic year 2017/2018, and (50) were selected as a sample for the study. The study followed the descriptive method, and used a questionnaire prepared for this purpose. The results of the study showed that the degree of the faculty members' awareness of educational competencies was very high within the principles of total quality. The results indicated that there was no statistically significant difference (α = 0.05) attributed to the variable of gender and (α = 0.05) attributed to the variable of experience. The study recommended that the administration of the university provide training workshops for the faculty members to update them of new teaching competencies in various fields, and to learn how to design online educational experiences. It also recommended conducting similar studies on other colleges and using different research tools. Keywords: Educational competencies, University of Jordan, Total quality, Faculty member.